(untitled) (Journal of Contemporary Issues in Accounting, 2023)
The study investigated the relationship between board characteristics and directors tunnelling of consumer goods companies in Nigeria. To achieve the objective, board characteristics key proxy variables were used in the study, namely board size and boards independent while directors tunnelling which is the dependent variable on the other hand is represented by director’s pay. Two hypotheses were formulated to guide the investigation and the statistical test of parameter estimates was conducted using Pearson Correlation Method. Ex-post facto research design was adopted and data for the study were obtained from the Nigerian Stock Exchange Factbook and the published annual financial reports of the selected consumer’s goods companies listed on Nigerian Stock Exchange (NSE) with data spanning from 2012 - 2019. Analyses of data indicated that board size is positive and has insignificant effect on tunnelling of quoted consumer’s goods companies in Nigeria; while board independent is negative, but does not have any significant effect on tunnelling of quoted consumer’s goods companies in Nigeria. The study suggests among others that in order to ensure the shareholders’ returns, corporate organizations such as consumer goods firms should be mindful of the appointment of the board members and such should be based on expertise, character and professional qualifications as well have more outside directors in the size of the board.